• Matéria: Matemática
  • Autor: Anônimo
  • Perguntado 6 anos atrás


 \sqrt{25 - 16}  +  \sqrt[16]{0}  -  \sqrt[3]{27}
PRECISO MUITO DA SUA AJUDA POR FAVOR!!!!!!​

Respostas

respondido por: laviniamariaz09
2

Resposta:

0

Explicação passo-a-passo:

 \sqrt{25 - 16}  +  \sqrt[16]{0}  -  \sqrt[3]{27}  \\  \sqrt{9}  + 0 - 3 \\ 3 + 0 - 3 \\ 0

respondido por: Makaveli1996
2

Oie, Td Bom?!

 =  \sqrt{25 - 16}  +  \sqrt[16]{0}  -  \sqrt[3]{27}

 =  \sqrt{25  - 16}  + 0 - 3

 =  \sqrt{25 - 16  } - 3

 =  \sqrt{9}  - 3

 =  3- 3

 = 0

Att. Makaveli1996

Perguntas similares